Bladder cancer-associated cancer-testis antigen-derived long peptides encompassing both CTL and promiscuous HLA class II-restricted Th cell epitopes induced CD4+ T cells expressing converged T-cell receptor genes in vitro. (3rd April 2018) - Tsuruta, Miki; Ueda, Shohei; Yew, Poh Yin; Fukuda, Isao; Yoshimura, Sachiko; Kishi, Hiroyuki; Hamana, Hiroshi; Hirayama, Masatoshi; Yatsuda, Junji; Irie, Atsushi; Senju, Satoru; Yuba, Eiji; et al.
ABSTRACT: DEP domain containing 1 (DEPDC1) and M-phase phosphoprotein 1 (MPHOSPH1) are human cancer testis antigens that are frequently overexpressed in urinary bladder cancer. In a phase I/II clinical trial, a DEPDC1- and MPHOSPH1-derived short peptide vaccine demonstrated promising efficacy in preventing bladder cancer recurrence. Here, we aimed to identify long peptides (LPs) derived from DEPDC1 and MPHOSPH1 that induced both T-helper (Th) cells and tumor-reactive cytotoxic T lymphocytes (CTLs). Stimulation of peripheral blood mononuclear cells (PBMCs) from healthy donors with the synthetic DEPDC1- and MPHOSPH1-LPs predicted to bind to promiscuous human leukocyte antigen (HLA) class II molecules by a computer algorithm induced specific CD4 + T cells as revealed by interferon-γ enzyme-linked immunospot assays. Three of six LPs encompassed HLA-A2- or -A24-restricted CTL epitopes or both, and all six LPs stimulated DEPDC1- or MPHOSPH1-specific Th cells restricted by promiscuous and frequently observed HLA class II molecules in the Japanese population. Some LPs are naturally processed from the proteins in DCs, and the capacity of these LPs to cross-prime CTLs was confirmed in vivo using HLA-A2 or -A24 transgenic mice. The LP-specific and HLA class II-restricted T-cell responses were also observed in PBMCs from patients with bladder cancer. Repeated stimulation of PBMCs with DEPDC1-LPs and MPHOSPH1-LPs yielded clonal Th cells expressing specific T-cell receptor (TCR)-α and β genes. These DEPDC1- or MPHOSPH1-derived LPs may have applications in immunotherapy in patients with bladder cancer, and the TCR genes identified may be useful for monitoring of Th cells specific to LPs in vivo .